LOT SIZING PROBLEM FOR FAST MOVING PERISHABLE PRODUCT: MODELING AND SOLUTION APPROACH - Sinha, Amit Kumar; Anand, Ankush (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
In this paper, the integrated lot sizing problem for perishable products is investigated. The problem is modeled as a single vendor multiple buyer system. A variant of the truckload discount scheme is applied and the proposed model is formulated as a mixed integer program (MIP). The traditional warehouses are replaced by ‘cross-docks’ and situations in which, cross-docking would be more beneficial are highlighted. The problem of fleet selection is also addressed and various strategies to minimize the vendor cost are discussed for centralized and decentralized supply chains. Sensitivity analysis performed on the input parameters underscores the significant impact of economies of scale in transportation on the total supply chain cost. Analysis of lead time-cost tradeoff reveals that alternate modes of transportation could be explored which reduces significantly the lead time of transportation, consequently reducing the total supply chain cost. The robust nature of the model formulation extends its application to scenarios with uncertain demands.